Perencanaan Pola Tanam berdasarkan Analisis Kebutuhan Air Tanaman dan Ketersediaan Air Irigasi - Tyasa, Rizal Bayu; Faradlillah Saves (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Indonesia, as a country heavily dependent on the agricultural sector, faces significant challenges regarding water availability, especially during prolonged dry seasons. The mismatch between crop water requirements and available irrigation water often leads to reduced agricultural productivity, particularly in areas with limited irrigation systems, such as the Wilangan Irrigation Area (DI) in Ponorogo Regency. This study aims to design an optimal cropping pattern by balancing crop water requirements and irrigation water availability in the DI Wilangan, Ponorogo Regency. The study aims to provide an efficient solution for irrigation management and cropping pattern planning. The method used in this study is a quantitative analysis utilizing hydrological and climatological data from 2014 to 2024. Water availability is calculated using the F.J. Mock method, while crop water requirements are estimated using the FAO Penman-Monteith method to determine reference evapotranspiration (ETo) and net irrigation demand. The results show that the PTT IV cropping pattern alternative, with a paddy-paddy-secondary crop pattern starting in the second period of December, results in the lowest water demand of 5.447 lt/second or equivalent to 0.0054 m³/second. The dependable discharge during this period reached 0.071308790 m³/s, ensuring that irrigation water needs can be fully met without deficit. Therefore, the PTT IV cropping pattern is recommended as the most efficient and sustainable option for irrigation water use in the area.